Black Rose - Roberts, Nora (New York Jove Books, 2005)
Three women meet at a crossroads in their lives, each searching for new ways to grow -- and find in each other the courage to take chances and embrace the future. Roz is a woman of independent means who thought love was behind her, but when romance takes her by surprise, she won't allow anything to keep her from her second chance at happiness.
Keywords: Widows -- Nurseries (Horticulture) -- Genealogists -- Tennessee